PERTIMBANGAN PEMBERIAN PENGURANGAN PAJAK BPHTB PADA PANDEMI COVID-19 - Raja Mohamad Rozi; Nisya (Warkat, 2021)
Tax is an obligatory contribution of the people to the state which functions to finance all public interests, including finance development to aims for the welfare of the people. The current condition of the Covid 19 pandemic provides a responsive idea to provide taxpayers with “relief” as regulated in Governor Regulation Number 103 of 2011 concerning Granting of Deductions, Relief and Exemption of Duty on Acquiring Rights on Land and Buildings (BPHTB). Pro contra arise in relation to criteria issue for granting relief conflicting regulations with the legal concept of the phrase "economic and / or financial crisis and natural disasters", as stipulated in the provisions of Article 3 paragraph (1), (2) points a and b as well as paragraph (3). In this regard, this article will discuss several things, including: How is the provision of tax breaks in certain circumstances such as "economic and / or financial crisis and natural disasters"? From the results of the discussion, severalthings were found: (1) The argument which is alleged to be the legal reason for not granting relief is derived from the “tax debt write-off doctrine” where that doctrine has been normalized in Article 1381 of the Civil Code; (2) The provisions of Article 3 paragraph (1) and paragraph (2) points a and b The phrase "economic and / or financial crises and natural disasters" regulate different customs, so that the pandemic-19 variable is not regulated in the two articles as a natural disaster. which caused theeconomic crisis, meaning that there was a lack of rules; and paragraph (3) The governor has the authority to regulate and interpret the situation.